2011
DOI: 10.1073/pnas.1103659108
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic electron partitioning between [FeFe]-hydrogenase and ferredoxin:NADP + -oxidoreductase (FNR) enzymes in vitro

Abstract: Photosynthetic water splitting, coupled to hydrogenase-catalyzed hydrogen production, is considered a promising clean, renewable source of energy. It is widely accepted that the oxygen sensitivity of hydrogen production, combined with competition between hydrogenases and NADPH-dependent carbon dioxide fixation are the main limitations for its commercialization. Here we provide evidence that, under the anaerobic conditions that support hydrogen production, there is a significant loss of photosynthetic electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 31 publications
5
126
0
Order By: Relevance
“…2), whose presence should decrease and increase the amplitude of the proton gradient, respectively. In this respect, it was recently shown that NADPH reduction by FNR prevents an efficient H 2 production by HYDA in vitro (Yacoby et al, 2011). This might be due to the low affinity of HYDA for FDX (K m = 35 mM; Happe and Naber, 1993), close to two orders of magnitude lower than the affinity of FNR for FDX (K m = 0.4 mM; Jacquot et al, 1997).…”
Section: Sequential and Transient Hydrogenase Activity And Psi-cef Comentioning
confidence: 95%
See 2 more Smart Citations
“…2), whose presence should decrease and increase the amplitude of the proton gradient, respectively. In this respect, it was recently shown that NADPH reduction by FNR prevents an efficient H 2 production by HYDA in vitro (Yacoby et al, 2011). This might be due to the low affinity of HYDA for FDX (K m = 35 mM; Happe and Naber, 1993), close to two orders of magnitude lower than the affinity of FNR for FDX (K m = 0.4 mM; Jacquot et al, 1997).…”
Section: Sequential and Transient Hydrogenase Activity And Psi-cef Comentioning
confidence: 95%
“…At the onset of illumination, only a hydrogenase-dependent LEF occurs (10 s), followed by the induction of PGRL1-dependent PSI-CEF and later the CBB cycle (120-240 s). When the CBB cycle has been activated by ATP, the NADP + pool is partially oxidized and FNR, being more efficient in competing for reduced FDX than hydrogenases (see next section; Yacoby et al, 2011), rapidly drives the entire electron flux toward CO 2 reduction (more than 360 s). In single mutants, increase in CBB cycle activity is only slightly delayed (Fig.…”
Section: Sequential and Transient Hydrogenase Activity And Psi-cef Comentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared in vitro reactions using Chlamydomonas thylakoid membranes, which harbor membrane-associated FNR activity (42). FDX1 mediated the highest rates of NADPH photo-production (7.896 mol of NADPH h Ϫ1 mg of Chl…”
Section: Physiological Assays Using Purified Recombinant Fdxs Fdx-drmentioning
confidence: 99%
“…Reactions using isolated Chlamydomonas thylakoid membranes (42) were prepared by adding purified recombinant HYDA1 (34) and purified recombinant FDX (see "Experimental Procedures"). We found that FDX1 drives the highest rates of hydrogen photo-production (0.52 nmol of H 2 h Ϫ1 ), although FDX2-mediated hydrogen photoproduction was 3-fold lower (0.18 nmol of H 2 h Ϫ1 ) (Fig.…”
Section: Fdx Driven Hydrogen Photo-productionmentioning
confidence: 99%